2020
DOI: 10.3892/ol.2020.11437
|View full text |Cite
|
Sign up to set email alerts
|

The roles of curcumin in regulating the tumor immunosuppressive microenvironment (Review)

Abstract: Cancer is a harmful threat to human health. In addition to surgery, a variety of anticancer drugs are increasingly used in cancer therapy; however, despite the developments in multimodality treatment, the morbidity and mortality of patients with cancer patients are on the increase. The tumor-specific immunosuppressive microenvironment serves an important function in tumor tolerance and escape from immune surveillance leading to tumor progression. Therefore, identifying new drugs or foods that can enhance the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 126 publications
(141 reference statements)
0
30
0
Order By: Relevance
“…Clinical studies using curcumin and its various formulations have shown that these drugs demonstrate a safety profile and have efficacious effects when used to treat patients diagnosed with chronic inflammatory joint pains. Finally, curcumin have anti-tumor effect and so would be a good drug candidate for CIPN treatment (no concerns by oncologists or patients about adverse effects and tumor growth) [ 106 ].…”
Section: Curcumin In Clinical Studies For Pnmentioning
confidence: 99%
“…Clinical studies using curcumin and its various formulations have shown that these drugs demonstrate a safety profile and have efficacious effects when used to treat patients diagnosed with chronic inflammatory joint pains. Finally, curcumin have anti-tumor effect and so would be a good drug candidate for CIPN treatment (no concerns by oncologists or patients about adverse effects and tumor growth) [ 106 ].…”
Section: Curcumin In Clinical Studies For Pnmentioning
confidence: 99%
“…This natural molecule also exhibits antibacterial, antifungal, antiviral, antiprotozoal, and antiparasitic properties [ 12 , 13 , 14 ]. Clinical trials have demonstrated the therapeutic benefits of curcumin supplementation in patients with inflammatory diseases (arthritis, inflammatory bowel disease, peptic ulcer, and H. pylori infection), metabolic syndrome, neurodegenerative diseases, and cancer, including colorectal, pancreatic, and breast cancers [ 11 , 15 , 16 , 17 , 18 ]. Due to the wide range of biological activities of curcumin and its pleiotropic therapeutic potential, this substance has been of great interest to researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, prolonged systemic inhibition of IKKβ by the Kinase Inhibitor of NF-κB-1 (KINK-1) agent, though ineffective when administered alone, potentiates the anti-cancer effect of a tumor vaccine in transplanted melanoma [87]. Another well-known, though poorly selective, IKK inhibitor, curcumin, decreases the number of intra-tumoral Treg cells in preclinical models of cancer [92][93][94], and enhances Th1 cells, while decreasing Treg cells in patients with lung and colon cancer [95,96]. Finally, c-Rel inhibition using the methylxanthine derivative Pentoxifylline (PTXF) or the selective c-Rel inhibitors, IT-603 or R96A, significantly reduces tumor growth and synergizes with anti-PD-1/Programed cell Death Ligand 1 (PD-L1) therapy as well as doxorubicin [26,[97][98][99].…”
Section: The Many Roles Of Nf-κb In Treg Cellsmentioning
confidence: 97%